The impact of Evidence-Based Pharmacy on the quality of pharmaceutical care: A survey study - Piotr Ratajczak; Barbara Jacieczko; Bartosz Kędziora; Dorota Kopciuch; Anna Paczkowska; Tomasz Zaprutko; Krzysztof Kus (PLoS ONE, 2025)
Applying Evidence-Based Pharmacy (EBPharm) principles is essential in pharmacy practice as it allows therapeutic decisions to be grounded in the best available scientific evidence. This approach enables pharmacists to provide patients with more effective and safer therapies, reducing the risk of adverse effects. This study assessed the EBPharm knowledge level among pharmacy professionals. Data were collected using a custom-designed online survey. The study also explored and defined the concept of EBPharm, offering insights into medical databases, types of scientific research, and evaluations of their quality and reliability. The study revealed widespread application of EBPharm principles among Polish pharmacy professionals, with significant associations between their use and factors such as professional experience (Chi² = 7.905518, p = 0.04801) and higher salaries. Respondents with formal EBPharm training demonstrated improved ability to evaluate scientific evidence (Chi² = 12.03125, p = 0.00244), while financial stability was linked to better systematic review skills (Chi² = 43.15693, p = 0.00000) and use of databases (Chi² = 63.14029, p = 0.00000). However, knowledge gaps remain, particularly among less experienced professionals, with only 30.35% of participants receiving formal training and 8.42% deeming it sufficient. Frequent use of informal sources by pharmacy technicians and limited familiarity with frameworks like PICO (Chi² = 37.65817, p = 0.00000) highlight the need for accessible, structured education. Targeted training, financial incentives, and greater reliance on reliable sources could enhance EBPharm integration, improving care quality and patient safety.